1982
DOI: 10.1002/app.1982.070270507
|View full text |Cite
|
Sign up to set email alerts
|

Character of crystallization nuclei in isotactic polypropylene

Abstract: SynopsisExamination of the isothermal crystallization and the effect of melting conditions on samples of isotactic polypropylene and its composite with talc, combined with electron-microscopic observation, has shown two types of heterogeneous nuclei effective in the crystallization process: (1) metastable nuclei, representing the unmelted crystalline phase of polypropylene, stabilized by solid heterogeneities, and operating after melting at relative low melting temperature and/or short melting time; and (2) st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(34 citation statements)
references
References 1 publication
1
33
0
Order By: Relevance
“…Beck and Ledbetter 11 stated that the supercooling, ‚T (‚T ϭ T m Ϫ T c ), i.e., the difference between the melting peak temperature and the crystallization peak temperature was a function of the overall rate of crystallization. Rybnikar 12,13 utilized the difference between the crystallization peak temperature of the nucleated polymer and that of virgin polymer, ‚T c , as a criterion for evaluating the nucleating effect. If ‚T c Ն 6.5°C, the nucleating efficiency was high.…”
Section: Resutls and Discussionmentioning
confidence: 99%
“…Beck and Ledbetter 11 stated that the supercooling, ‚T (‚T ϭ T m Ϫ T c ), i.e., the difference between the melting peak temperature and the crystallization peak temperature was a function of the overall rate of crystallization. Rybnikar 12,13 utilized the difference between the crystallization peak temperature of the nucleated polymer and that of virgin polymer, ‚T c , as a criterion for evaluating the nucleating effect. If ‚T c Ն 6.5°C, the nucleating efficiency was high.…”
Section: Resutls and Discussionmentioning
confidence: 99%
“…It can be seen from Table 1 that super-cooling degree ( T) of iPP nucleated with HPN-68 was much less than that of virgin iPP, which indicates that addition of HPN-68 greatly increases the crystallization rate of iPP. Rybnikar [22,23] adopted the difference between the crystallization peak temperature (T c ) of the nucleated polypropylene and that of virgin polypropylene, T c , as a criterion for evaluating the nucleation efficiency. The nucleation efficiency was high for T c ≥ 6.5 • C, medium for T c = 5∼6.5 • C and low for a difference of 3-5 • C. This method for evaluating nucleation efficiency was consistent with the method of classifying nucleation efficiency according to the spherulite size observed by microscopy (high nucleation efficiency for mean size of spherulites less than 50 µm; medium nucleation efficiency for 50-100 µm of mean size and low nucleation efficiency for 100-200 µm mean size).…”
Section: Tablementioning
confidence: 99%
“…8,[9][10][11][12] Numerous results are also reported on glass fiber/iPP composites concerning transcrystallization phenomena, many of them being conIt is known that the presence of a solid surface flicting. It was recently shown that the transcrys-(substrate) in contact with thermoplastic polytalline zone appeared only if the glass fiber is mers during the crystallization from the melt genpulled out from the polymer melt or when shear eraly favors the heterogeneous nucleation 1,2 and stress is applied at given crystallization temperaoften a growth of the transcrystalline zone.…”
Section: Introductionmentioning
confidence: 99%